Time-lapse photography for geologic research - Fahnestock, Robert K., 1932-, author; Colorado State University, publisher (Colorado State University. Libraries, 1961)
Developments in photographic equipment have made it possible to design a wide variety of time-lapse equipment to photograph and measure geologic processes. New films, exposure controls and techniques promise better photography under diverse light conditions. Application of photogrammetry to time-lapse analysis will allow measurement of rate of change of distance, elevation, and direction.
CER61RKF6.
Approved for publication by Director, U.S. Geological Survey.
January 1961.
Keywords: Photography in geology; Geology -- Photographs; Chronophotography